Asuhan Kebidanan Komprehensif Pada Ny. M Umur 44 Tahun G4P2A1 Faktor Resiko Umur Ibu Lebih Dari 35 Tahun Dan Pre-Eklamsia Di Wilayah Kerja Puskesmas Paguyangan Tahun 2023 - Dais Maesadillah; Endang Susilowati; Widi Astuti (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
The Program Registration at the Ministry of Health in 2020 shows a figure of 5,125 deaths. AKI is caused by bleeding, pre-eclampsia/eclampsia, infection, late arrival of the mother to a health facility and mothers with positive PCR/Antigen. The aim of this research is to be able to implement comprehensive midwifery care for Mrs. M, 44 years oldhe maternal mortality rate in Indonesia compiled from the Family Health. This research method used quantitative descriptive with a case study approach. The case study carried out was in the form of Comprehensive Midwifery Care which examined women during pregnancy, childbirth, newborns, postpartum and family planning with Varney's seven-step midwifery management and SOAP. Comprehensive Midwifery Care for Mrs. M, namely during pregnancy, pre-eclampsia was discovered. Delivery by Sectio Caesarea and the baby was born normally. During the postnatal period, no problems were found in the baby. During the postpartum period, no problems were found. Mother uses MOW birth control. Based on the care, it is concluded that the care has been implemented according to Midwifery Service standards.